Climate security and religion in Africa: Towards sustainable development goals - Tarusarira, Joram (Palgrave Macmillan, 2023)
Climate impacts in Africa contribute to climate-related security risks in numerous pathways. Most of the research on climate security has been carried out in Africa, where the population is highly religious and, in some cases, treats natural resources as sacred. In addition, when climate-related conflicts ensue, groups may form alliances along religious lines of difference. However, religion is conspicuously absent in the discourse. The literature has a consensus that there is no direct link between climate change and conflict. Climate change does not cause conflict but contributes to climate security risks in combination with other factors. Because of this consensus, the discussion has begun to shift the focus of inquiry, language and register to talk about the relationship between climate and security from identifying linear causal linkages to developing a more nuanced understanding of this relationship in general. Mediating and moderating factors, thus, can explain how climate change promotes or undermines climate-related security risks. This chapter takes a focused analysis of religion as one hitherto absent variable in the climate security discourse.